2021
DOI: 10.1007/s11240-021-02193-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction and submerged cultivation of Valeriana jatamansi adventitious root cultures for production of valerenic acids and its derivatives

Abstract: In vitro adventitious roots were induced from Valeriana jatamansi to assess their quality as an alternative ingredient for extraction of secondary metabolites to meet the demand of phytopharmaceutical industries. A signi cantly (p ≤ 0.05) high root induction (90 %) was achieved on Schenk and Hildebrandt medium forti ed with 9.84 µM indole-3-butyric acid. A maximum root biomass (144.09 ± 11.36 g/L) with high relative growth rate (2.01 ± 0.04) and growth index (13.41) was achieved in submerged cultivation. The t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Another study reported that adventitious root cultures of Valeriana jatamansi Jones ex Roxb. accumulated 451.85 µg g DW −1 total phenolic compounds, predominantly composed of kaempferol and rutin [55]. Rutin was also described in elicited cell suspension cultures of Momordica charantia L. at a concentration of 352 µg g DW −1 [56].…”
Section: Flavonoid Glycosides From Organs and Tissue Cultures Of Tili...mentioning
confidence: 93%
“…Another study reported that adventitious root cultures of Valeriana jatamansi Jones ex Roxb. accumulated 451.85 µg g DW −1 total phenolic compounds, predominantly composed of kaempferol and rutin [55]. Rutin was also described in elicited cell suspension cultures of Momordica charantia L. at a concentration of 352 µg g DW −1 [56].…”
Section: Flavonoid Glycosides From Organs and Tissue Cultures Of Tili...mentioning
confidence: 93%
“…Sharma and Mondal [ 102 ] studied the field performance of V. jatamansi and found that room-dried roots from higher altitudes contained 0.426% valerenic acid as compared to the lower altitude (0.186%). Gehlot et al [ 103 ] studied the production of valerenic acids under the submerged cultivation of V. jatamansi and found that a higher accumulation of valerenic acid (1525.14 μg/g) was in plant rhizomes whereas acetoxyvalerenic acid (543.91 μg/g) and hydroxyl valerenic acid (919.57 μg/g) was higher in adventitious roots. It was also found that the maximum fresh root biomass was with half-strength Schenk & Hildebrandt medium having 2% sucrose and 4.92 μM IBA.…”
Section: Diversity and Variationsmentioning
confidence: 99%
“…In particular, the highest root FW (470.00 g/L medium), DW (17.41 g/L medium), RGR (0.76), and growth index (20.22) were obtained from cultures fed with 45 g/L sucrose. Undoubtedly, sucrose is considered one of the essential carbon sources for the plant; easily catabolized by plant tissues into glucose and fructose, provides energy rapidly, and participates in cell growth and development (Gehlot et al, 2022). The study of Sivanesan and Jeong (2009) also reported a decline in root growth of Plumbago zeylanica when sucrose was replaced with fructose or glucose in the root culture medium.…”
Section: Effect Of Sugar Types and Levels On Root Biomass Saponin And...mentioning
confidence: 99%
“…Moreover, root culture shows high stability, high proliferation with fast growth, and a copious content of bioactive metabolites (Matvieieva et al, 2022). In recent reports, in vitro root cultures produced greater amounts of phytoconstituents than donor plant, as well as compounds not located in the intact plants (Gehlot et al, 2022). Root cultures can be divided into two groups -non-transformed and transformed or transgenic root (hairy root) cultures which are transformed by Rhizobium rhizogenes bacteria (formerly known as Agrobacterium rhizogenes) (Li et al, 2016;Gabr et al, 2019).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%